Socialization on the Preparation of Natural Plant Growth Regulator to an Organic Farming Community in Lengkong Village, Ponorogo Regency - Saefur Rohman; Nova Triani (Future Science, 2022)
The awareness of the negative impact of conventional farming and its safety have increased society’s perception of organic farming and its product. Unfortunately, the level of knowledge and adoption of organic farming practices among farmers are still low due to the assumption that organic farming is hard to implement. Ponorogo Organic Farming Community is a farming community that tries to adopt an organic farming system and has produced paddy and several horticultural crops cultivated organically. It was identified that the community had not yet applied the use of natural plant growth regulators (PGR) in their practice. Therefore, an agricultural extension activity was organized to share the knowledge on how to prepare an onion extract natural PGR. A survey was also performed to understand the level of knowledge and adoption of the participant. The questionnaire showed that most of the participants had not ever applied natural PGR even though had already heard about them before. Therefore, this program was of relevancy to improve the knowledge of the participant on organic way of farming particularly on the utilization of natural PGR.